DETERMINANTS OF RURAL AND URBAN LAND AND BUILDING TAXPAYER COMPLIANCE IN MAMUJU REGENCY - Hasri Hasri; Asri Usman; Darmawati Darmawati (SEAN Institute, 2022)
This study aims to analyze the effect of tax justice, tax sanctions and taxpayer knowledge on taxpayer compliance with taxpayer awareness as a moderating variable. This type of research is comparative causal, which uses primary data with a questionnaire. The research population is taxpayers who receive notification of tax payable in Mamuju of 102,265 taxpayers. The sample in this study was calculated using the Slovin formula with a tolerance value of 10%, which is 100 samples (50 taxpayers who comply with paying taxes and 50 taxpayers who do not comply with paying taxes). Data analysis using SmartPLS 3.0 software. The results of the study show that tax justice has no effect on taxpayer compliance, tax sanctions and taxpayer knowledge have an effect on taxpayer compliance. Taxpayer awareness is not able to moderate the relationship between tax justice and taxpayer compliance. Taxpayer awareness is able to moderate the relationship between tax sanctions and taxpayer knowledge with taxpayer compliance.